Electrospun MXene/carbon nanofibers as supercapacitor electrodes. Issue 1 (5th December 2018) - Levitt, Ariana S.; Alhabeb, Mohamed; Hatter, Christine B.; Sarycheva, Asia; Dion, Genevieve; Gogotsi, Yury
Abstract : MXene/carbon composite electrodes with high loadings of MXene were prepared via electrospinning. These flexible and free-standing electrodes exhibit high areal capacitance relative to pure carbon nanofibers and MXene-coated fibers and textiles. Abstract : Free-standing Ti3 C2 T x MXene/carbon nanofiber electrodes are prepared via electrospinning Ti3 C2 T x MXene flakes with polyacrylonitrile (PAN) and carbonizing the fiber networks. Using this simple fabrication method, delaminated MXene flakes are embedded within carbon nanofibers and these fiber mats are used as electrodes without binders or additives. Unlike coated electrodes, which may suffer from the active material delaminating from the substrate during folding or bending, composite electrodes are stable and durable. Previous attempts to incorporate Ti3 C2 T x MXene into electrospun fibers resulted in low mass loadings, ∼1 wt% Ti3 C2 T x MXene. In this work, MXene flakes are added into PAN solutions at a weight ratio of 2 : 1 (MXene : PAN) in the spinning dope, producing fiber mats with up to 35 wt% MXene. Composite electrodes have high areal capacitance, up to 205 mF cm −2 at 50 mV s −1, almost three times that of pure carbonized PAN nanofibers (70 mF cm −2 at 50 mV s −1 ). Compared with electrospun nanofibers spray-coated with Ti3 C2 T x, these composite fibers exhibit double the areal capacitance at 10 mV s −1 . This method can be used to produce MXene composite fibers using a variety of polymers, which have potential applications beyond energy storage, including filtration, adsorption, and electrocatalysis, where fibers with high aspect ratio, accessible surface, and porosity are desirable.